Surgical and orthodontic treatment of severely intruded permanent incisors: A case report - Koogi Sonoda, Celso [UNESP]; Rahal, Vanessa [UNESP]; Caliente, Eliana Aparecida [UNESP]; Beija Flor Figueiredo, Cássio Messias [UNESP]; Figueiredo, Leonardo Raniel [UNESP]; Palhano Freire, Julliana Cariry; Dias-Ribeiro, Eduardo (My University, 2019)
Traumatic dental intrusion is a serious injury and results in significant damage to the periodontal ligament, dentin-pulp complex, and alveolar bone. This article presents a case of severe intrusion of the two upper permanent central incisors where the treatment option was the combination of the surgical and orthodontic technique. The difficulty of accessing the crowns of these teeth to bond the brackets was solved by lifting a full thickness flap. To disengage the teeth from the alveolus, a careful dislocation motion was performed. After suturing the flap, a removable orthodontic appliance was installed and an extrusive force was applied for 8 weeks. After 10 weeks, the endodontic treatment was performed and the crowns were restored. The 10-year clinical control showed normal mobility. Radiographically, minor losses of the cervical alveolar cortical bone and integrity of the periodontal ligament were observed.
Keywords: Dental trauma; Intrusive luxation; Orthodontic extrusion